2021
DOI: 10.3390/jcs5030085
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Quantum Capacitance of Niobium Nitrides Nb2N and Nb4N3 for Supercapacitor Applications

Abstract: The density of states and quantum capacitance of pure and doped Nb2N and Nb4N3 single-layer and multi-layer bulk structures are investigated using density functional theory calculations. The calculated value of quantum capacitance is quite high for pristine Nb2N and decent for Nb4N3 structures. However for cobalt-doped unpolarized structures, significant increase in quantum capacitance at Fermi level is observed in the case of Nb4N3 as compared to minor increase in case of Nb2N. These results show that pristin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“… 104 The maximum C Q has been observed for Nb 2 N (1196.28 μF/cm 2 at −1 V and 844.8 μF/cm 2 at 0.5 V) and Nb 4 N 3 (174.86 μF/cm 2 ). 105 Remarkably, increasing the number of layers has profound effects on enhanced C Q for both Nb 2 N and Nb 4 N 3 .…”
Section: Mxenementioning
confidence: 97%
See 1 more Smart Citation
“… 104 The maximum C Q has been observed for Nb 2 N (1196.28 μF/cm 2 at −1 V and 844.8 μF/cm 2 at 0.5 V) and Nb 4 N 3 (174.86 μF/cm 2 ). 105 Remarkably, increasing the number of layers has profound effects on enhanced C Q for both Nb 2 N and Nb 4 N 3 .…”
Section: Mxenementioning
confidence: 97%
“…We highlight that simulated C Q of NbN at negative and positive biases is found to be 834.5 and 1683.7 F/g compared to Nb 4 N and Nb 5 N 6 . The maximum C Q has been observed for Nb 2 N (1196.28 μF/cm 2 at −1 V and 844.8 μF/cm 2 at 0.5 V) and Nb 4 N 3 (174.86 μF/cm 2 ) . Remarkably, increasing the number of layers has profound effects on enhanced C Q for both Nb 2 N and Nb 4 N 3 .…”
Section: Mxenementioning
confidence: 99%
“…It has been demonstrated that cobalt doping can increase the capacitance of niobium nitride. Bharti et al calculated the C Q of Nb 2 N and Nb 4 N 3 and investigated the effect of Co-doping on their C Q [ 128 ]. Their calculations show that the C Q value of Nb 2 N is remarkably high (1196.28 μF/cm 2 , −1 V) and the C Q of Nb 4 N 3 is much lower than that of Nb 2 N. When they increased the number of layers of Nb 2 N and Nb 4 N 3 , they found that the C Q kept increasing with the more layer numbers.…”
Section: Research Progress Of 2d Electrode Materials For Edlcsmentioning
confidence: 99%
“…Hence, materials with high quantum capacitance are more suitable for fabrication of supercapacitors. So, it becomes important to calculate and study the QC of the materials suggested for supercapacitor applications [9][10][11]. Researchers have tried modifying graphene structure by doping or functionalization [12] to increase its QC value but still the specific capacitance of graphene electrodes is not very high.…”
Section: = + [1]mentioning
confidence: 99%